2020
DOI: 10.1002/erv.2757
|View full text |Cite
|
Sign up to set email alerts
|

The autism diagnostic observation schedule: Patterns in individuals with anorexia nervosa

Abstract: Objective Studies have used the Autism Diagnostic Observation Schedule (the ADOS‐2) in individuals with anorexia nervosa (AN), but the patterns of scores have not been assessed. We examined which subset of the ADOS‐2 items best discriminate individuals with AN from healthy controls (HC), and assessed the potential clustering of AN participants based on different profiles of the ADOS‐2 item scores. Method We combined datasets from two previous studies, and (a) compared mean ranks between young AN participants (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 34 publications
4
14
0
Order By: Relevance
“…Although women with ASD also report similar difficulties with exclusion and anxiety, they also report frequent mistakes and misunderstandings of typical social conventions [ 23 ]. While patients with AN often appear withdrawn and socially anxious, it seems that only a minority of patients show difficulties in understanding the to and fro of conversation, or with responding appropriately to social prompts [ 64 ]. These individuals may indeed meet diagnostic criteria for ASD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although women with ASD also report similar difficulties with exclusion and anxiety, they also report frequent mistakes and misunderstandings of typical social conventions [ 23 ]. While patients with AN often appear withdrawn and socially anxious, it seems that only a minority of patients show difficulties in understanding the to and fro of conversation, or with responding appropriately to social prompts [ 64 ]. These individuals may indeed meet diagnostic criteria for ASD.…”
Section: Discussionmentioning
confidence: 99%
“…This approach was used in a previous study addressing a similar research question [ 63 ]. TD were not included in the item endorsement analyses, as discriminating between ASD and TD, as well as AN and TD using the ADOS-2 was not the purpose of this study and has been covered elsewhere [ 52 , 53 , 64 ]. A significance level of α = 0.01 was used across analyses, however no correction was applied to account for multiple comparisons [ 65 ].…”
Section: Methodsmentioning
confidence: 99%
“…Another key finding of this study is that although adolescents with AN were found to score significantly higher than HCs on the SRS, the scores were not high enough to meet the indicated cut-off point for ASD. While these difficulties may not be severe enough to diagnose ASD, they could still leave an individual vulnerable to the development of AN ( 48 ) and may have impact on treatment outcome, making them clinically relevant ( 7 , 11 , 49 ). Although the SRS, has been established to have high reliability and validity, to be significantly correlated with the diagnosis of autism made using the Autism Diagnostic Interview-Revised and can be used with the aim of evaluating autism-like symptom clusters ( 32 , 50 , 51 ), it has not previously been used to determine autistic traits in adolescents with AN.…”
Section: Discussionmentioning
confidence: 99%
“…Both conditions share a common profile of resistance to changes, social withdrawal and social disengagement, and show similar patterns of neurocognitive dysfunction including impaired set-shifting, weak central coherence, and impaired theory-of-mind (ToM) abilities ( 6 , 9 ). Patients with AN have also poor social and emotional functioning ( 10 , 11 ), including interpersonal relationship problems ( 7 ), reduced facial emotion expression ( 12 ), impaired facial emotion recognition ( 13 ), difficulties identifying emotions ( 10 ) and social anhedonia ( 3 ). As a result, the studies based on experimental data and clinical observations show that these cognitive, socio-emotional and interpersonal problems may be both a cause and a contributing factor in the course of the disease ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation